Symposium 1: Semantic Web Learning Technology Design: Addressing Pedagogical Challenges and Precarious Futures - Carmichael, Patrick (Proceedings of the International Conference on Networked Learning, 2016)
Semantic web technologies have the potential to extend and transform teaching and learning, particularly in those educational settings in which learners are encouraged to engage with ‘authentic’ data from multiple sources. In the course of the ‘Ensemble’ project, teachers and learners in different disciplinary contexts in UK Higher Education worked with educational researchers and technologists to explore the potential of such technologies through participatory design and rapid prototyping. These activities exposed some of the barriers to the development and adoption of emergent learning technologies, but also highlighted the wide range of factors, not all of them technological or pedagogical, that might contribute to enthusiasm for and adoption of such technologies. This suggests that the scope and purpose of research and design activities may need to be broadened and the paper concludes with a discussion of how the tradition of operaismo or ‘workers’ enquiry’ may help to frame such activities. This is particularly relevant in a period when the both educational institutions and the working environments for which learners are being prepared are becoming increasingly fractured, and some measure of ‘precarity’ is increasingly the norm.